2021
DOI: 10.1088/1361-6463/ac0070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a kHz sinusoidal Argon plasma jet impinging on water using Thomson scattering and fast imaging

Abstract: The electron dynamics in a stable and non-filamentary Argon plasma jet, generated using AC excitation at kHz frequencies and interacting with a liquid surface either at floating potential or electrically grounded were examined using laser Thomson scattering. In the case of a floating liquid, two discharge events were observed during each half-cycle of the applied sinusoidal voltage. In the grounded liquid case only one discharge event was observed, which occurred during the positive half period. Through spatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…The influence of the grounding conditions of a target under plasma exposure has been examined before regarding the electronic properties of the discharge. For a different coaxial-plasma jet operated using argon gas instead of helium and 5 s pulses (16 kHz), it was shown that the resistance of a conductive liquid target towards the ground determines whether it behaves as a DBD-type discharge (for a high impedance path to ground) or a DC-type (low impedance path to ground) 20 , 28 . This had significant consequences for the temporal dynamics of electron density and temperature in the center of the plasma plume.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the grounding conditions of a target under plasma exposure has been examined before regarding the electronic properties of the discharge. For a different coaxial-plasma jet operated using argon gas instead of helium and 5 s pulses (16 kHz), it was shown that the resistance of a conductive liquid target towards the ground determines whether it behaves as a DBD-type discharge (for a high impedance path to ground) or a DC-type (low impedance path to ground) 20 , 28 . This had significant consequences for the temporal dynamics of electron density and temperature in the center of the plasma plume.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the recombination coefficient ( β ) equals to 10 −7 cm 3 /s for argon discharge, [ 39 ] and ne0 ${<mpadded xmlns="http://www.w3.org/1998/Math/MathML">n</mpadded>}_{e}^{0}$ is in the range 10 13 −10 15 cm −3 for streamers. [ 82–84 ] Resultantly, τ r is 1.0 μs at most, which is several orders of magnitude shorter than a voltage cycle ( T = 0.5 ms). Therefore, residual electrons can be neglected.…”
Section: Resultsmentioning
confidence: 96%
“…Since, the charge due to the ions in the water are non-relativistic, the scattering of EM waves can probe charge analogous to the Thomson scattering, Rayleigh Scattering phenomenon etc The Thomson scattering has been explored in the plasma interaction with liquid surface in floating potential and grounded. The electron dynamics from the plasma to the liquid is studied with the Thomson scattering [31]. The non-equilibrium plasma at atmospheric pressure in contact with the liquid to study the vaporized water in contact [32].…”
Section: Introductionmentioning
confidence: 99%